Preoperative Warming Versus no Preoperative Warming for Maintenance of Normothermia in Women Receiving Intrathecal Morphine for Cesarean Delivery: A Single Blinded, Randomized Controlled Trial. Issue 4 (December 2017) - Munday, J.; Osborne, S.; Yates, P.; Sturgess, D.; Jones, L.; Gosden, E.
Abstract : ( Anesth Analg . 2017 May 12)[Epub ahead of print] Rates of perioperative hypothermia, which has been associated with detrimental physiological effects in nonpregnant women, can be as high as 80%. Therefore, in the present study, the authors evaluated the effectiveness of a 20-min period of perioperative forced air warming on maternal temperature compared to no warming in women receiving intrathecal morphine during elective cesarean delivery.